Discuss The Effect of The Third Organizational Efficiency Theory on Society and Economic Growth Via Depravity Axes Frustration by A Non-Linear Model (Depravity Aspects Benefits) - Seddek, Laila F.; Abed, Ahmed M. (International Journal of Membrane Science and Technology, 2023)
TBL elements’ prosperity means saving and growth of the Triple bottom line, which are People, Profit, and Planet. Therefore, this work focuses on analyzing the effect of depravity over prosperity via citizen satisfaction level (CSL) and prosperity growth indicator (PGI) through spreading questionnaires addressing the productive and service companies in Egypt. The authors link CSL and PGI with minimizing service time and maximizing income parameters respectively and tracking prosperity via non-collinear productivity growth model with threshold effects. Therefore, argue that depravity resultin administrative, technician, and financial failure, which can be controlled by empirical proposed Automated Governance Self-Management (AGSM). The organizations’ productivity has been tracked by the development efficiency index (DEI), which reflects depravity resistance level using smart poka-yoke ( ). The responses to the questionnaires discover that administrative depravity has two faces, one emphasizes its benefit on facilitating and speeding up the procedures, while the other is adverse and reduces the economic growth rate. The authors advocate changing administrative policies from centralization to traceable decentralization backed by delegation and economic liberty via controlling all activities according to time.